DAMPAK PROJECT-BASED LEARNING (PJBL) BERBASIS ETNO-STEM TERHADAP KETERAMPILAN BERPIKIR KREATIF MURID - Nanda Nur Kumairoh, Diah; Fauzi Hendratmoko, Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low creative thinking skills of students in science learning encourages innovation in teaching. Learning with the Ethno-STEM based PjBL model has the potential to improve creative thinking skills through the application of Ethno-STEM based PjBL. This study used a one group pre-test post-test design, involving 32 eighth-grade students at SMP Sunan Giri Menganti. The research instrument was a pre-test post-test question sheet. The data were analyzed quantitatively using paired sample t-test, N-gain, and effect size to measure the improvement of creative thinking skills. The results of the study showed an increase in scores between the pre-test and post-test. With an average N-gain of 0.60, which falls into the moderate category, and an effect size of 3.76, indicating a large effect. The conclusion of this study is that the application of the Ethno-STEM based PjBL model is effective in improving students' creative thinking skills.